Carrageenan based printable magnetic nanocomposites for actuator applications - Macedo, V. M. (2022)
The digitalization of the society in the context of the Internet of Things (IoT) demands a new generation of sustainable materials and processes to reduce the environmental impact of technological advances. This work reports on sustainable multifunctional nanocomposites based on carrageenan and magnetic cobalt ferrite (CoFe2O4-CFO) nanoparticles, processed by direct-ink-writing and on their applicability as magnetic actuators. The nanocomposites exhibit a compact morphology with CFO nanoparticles well distributed within the polymer matrix. The incorporation of CFO nanoparticles significantly improves the thermal and mechanical properties of the polymer: the onset degradation temperature increases 30ºC and the Young's modulus increases from 1 MPa in the pristine polymer to 17 MPa for the composite with 5 wt.% CFO content. CFO magnetic nanoparticles are also responsible for increasing the dielectric constant of carrageenan from ≈1000 up to ≈9000 (10wt.% CFO composite), and for the magnetic properties, with a maximum magnetization of ≈16 emu.g -1 and coercive field of ≈3.4 kOe in the 30 wt.% CFO composite. A magnetic actuator has been developed with excellent maximum displacement.